Implementasi Riyadhah dalam Membentuk Pribadi Ikhlas pada Santri Pondok Pesantren - Yanti Nurdiyanti; Ujang Sutaryat (Bidayatuna, 2023)
To build a noble personality in the process of Islamic education, it is necessary to carry out consistent and sustainable coaching. One way to build a sincere personality is through coaching the mental aspect. The form of mental aspect development is through riyadhah. The method used is qualitative with a case study approach. Data collection techniques were carried out using interviews and documentation. Data analysis using miles and hubarman model. As well as the validity test using the credibility test with the triangulation method.The results of the study show that the implementation of Riyadhah at the Riyadlusharfi Walmantiq Islamic Boarding School is in the form of habits that are mandatory to be followed by all students at the Riyadlusharfi Walmantiq Islamic Boarding School, namely; 1) Congregations perform the five daily prayers at the mosque, 2) wiridan, 3) the habit of reading the Qur'an, 4) praying the dhuha circumcision, 5) praying the tahajjud circumcision, 6) fasting circumcision on Mondays and Thursdays. These routine activities are carried out continuously starting with the intention of Allah. In implementing the concept of riyadhah, each activity is given practical guidance which is carried out based on four principles; 1) carrying out activities starting with prayer, 2) intending for worship alone, 3) following the demands of the Shari'a in their activities and 4) punishment for violations is not materialistic.